Enhancing lower-limb rehabilitation: a scoping review of augmented reality environment - Yuanyuan Liu; Qiong Zhang; Weiyi Li (Journal of NeuroEngineering and Rehabilitation)
Abstract Background Lower-limb rehabilitation is crucial for restoring motor function in individuals with physical impairments; however, traditional rehabilitation approaches often encounter challenges such as limited resources and reduced patient motivation. Augmented reality (AR) offers an innovative approach by enriching rehabilitation with interactive and engaging experiences, thereby enhancing both motivation and treatment outcomes. AR environments enable patients to practice exercises in an immersive setting that emulates real-life scenarios, potentially increasing adherence and improving functional recovery. Methods This scoping review analyzed 25 peer-reviewed studies on the use of AR within the “Environment” component of the Human–Computer-Environment system for lower-limb rehabilitation. We present a taxonomy of existing AR systems, categorizing them by rehabilitation tasks (content) and interaction modes (form), which identify both physical and virtual elements that contribute to a supportive AR environment. Discussion The findings suggest that well-designed AR environments offer a flexible and cost-effective approach to various rehabilitation tasks. Customization is essential for addressing specific rehabilitation stages, including muscle strengthening, balance improvement, and gait training. The integration of multisensory feedback, such as visual, auditory, and haptic cues, enhances patient engagement and provides real-time performance monitoring. Effective AR environments must also account for the distinct needs of each limb, particularly for bilateral impairments, and ensure sufficient space for safe movement. By providing an individualized rehabilitation experience, AR environments have the potential to significantly improve patient motivation and outcomes. Future research should explore the integration of AR environments with assistive technologies, such as wearable devices and exoskeletons, to further enhance rehabilitation possibilities.